2003
DOI: 10.1162/105474603765879567
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Serves as a Support Technology in Cardiopulmonary Exercise Testing

Abstract: A b st r a ctThe purpose of this study was to develop a virtual cycling system and examine the in uence of virtual reality (VR) on test performance during clinical exercise testing. We aimed to compare the physiological responses of the cardiovascular and ventilatory systems during incremental exercise testing with or without VR, and to measure VR effects on the ratings of perceived exertion (RPE) and cycling duration throughout the test.Twelve healthy senior citizens (ten men and two women) with a mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…However, until recently, very few studies examined whether VR stationary exercise bike equipment truly promotes a dissociation attentional focus and enhances enjoyment of the experience. Indeed, few studies have directly tested the effect of a VR setting on affective states and/or performance during indoor cycling (Annesi & Mazas, 1997;Chuang et al, 2003;Huang, Tsai, Sung, Lin, & Chuang, 2008;IJsselsteijn, De Kort, Westerink, De Jaggerand, & Bonants, 2006;Mac Rae, Miller-Perrinand, & Tinberg, 2003;Plante, Aldridge, Ogden, & Hanelin, 2003;Plante, Frazier, et al, 2003). Annesi and Mazas (1997) tested the effect of a 14-week VR exercise bicycle program in a fitness center on adherence and exercise-induced feeling states among 45 adults, aged between 20 and 60 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, until recently, very few studies examined whether VR stationary exercise bike equipment truly promotes a dissociation attentional focus and enhances enjoyment of the experience. Indeed, few studies have directly tested the effect of a VR setting on affective states and/or performance during indoor cycling (Annesi & Mazas, 1997;Chuang et al, 2003;Huang, Tsai, Sung, Lin, & Chuang, 2008;IJsselsteijn, De Kort, Westerink, De Jaggerand, & Bonants, 2006;Mac Rae, Miller-Perrinand, & Tinberg, 2003;Plante, Aldridge, Ogden, & Hanelin, 2003;Plante, Frazier, et al, 2003). Annesi and Mazas (1997) tested the effect of a 14-week VR exercise bicycle program in a fitness center on adherence and exercise-induced feeling states among 45 adults, aged between 20 and 60 years.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, few studies have directly tested VR effects on exercise performance. Indeed, in a recent paper Huang et al (2008) report that VR feedback actually enables anaerobic exercise for longer duration by reducing perceived exertion (see also Chuang et al, 2003). However, these two studies were conducted in a rehabilitation (poststroke) context that may not be easily generalized to nonpathologic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Chuang et al [38] compared physiological responses of the cardiovascular and respiratory systems during incremental exercise testing with and without VR in healthy older adults. A mechanically braked bicycle was linked to a visual virtual scene projected on a flatscreen display.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar scenario, researchers demonstrated that if participants' cycling speed was depicted in a biking game on a computer screen in front of them, they reported increased enjoyment and energy and reduced tiredness compared to participants who cycled with no virtual biking game or who just played the virtual biking game (Plante, Aldridge, Bogden, & Hanelin, ). Following up, Chuang and colleagues () demonstrated that participants who exercised while in a VE cycled longer, further, and had more calorie consumption than participants who cycled in a normal environment. Finally, when compared to participants who walked outdoors or walked indoors on a treadmill, participants who walked indoors on a treadmill while a video of the outdoors was projected on a screen in front of them were most relaxed and experienced the least tension (Plante, Cage, Clements, & Stover, ).…”
Section: The Obesity Epidemic and Intervention Effortsmentioning
confidence: 99%